2016
DOI: 10.1620/tjem.239.47
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Decrease in Platelet Counts Is Associated with Delayed Liver Function Recovery and Complications after Partial Hepatectomy

Abstract: Peripheral platelet counts decrease after partial hepatectomy; however, the implications of this phenomenon are unclear. We assessed if the observed decrease in platelet counts was associated with postoperative liver function and morbidity (complications grade ≤ II according to the Clavien-Dindo classification). We enrolled 216 consecutive patients who underwent partial hepatectomy for primary liver cancers, metastatic liver cancers, benign tumors, and donor hepatectomy. We classified patients as either low or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…A further 611 articles were excluded for various reasons, such as irrelevant studies, experimental studies or review articles. After reading the remaining 103 articles, 16 studies were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 611 articles were excluded for various reasons, such as irrelevant studies, experimental studies or review articles. After reading the remaining 103 articles, 16 studies were included in the qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Predicting risk factors for PHLF plays a vital role in planning a patient's perioperative course and decreasing liver‐related mortality after hepatectomy. A review of the literature showed that PHLF rates range from 0 to 43·1 per cent, and mortality rates between 0·5 and 15·6 per cent. This variation can be explained by use of different definitions of PHLF, different time points for mortality, and variability in the degree of hepatectomy, which led to clinical heterogeneity between included studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, experimental studies have demonstrated that platelets play an important role in promoting liver regeneration after hepatectomy. One clinical study demonstrated that a decrease of the postoperative platelet percentage to below 60% after hepatectomy was associated with delayed liver function recovery and postoperative morbidity (45). Although platelet counts reached a minimum on POD 3 for all patients (45), when platelet counts returned to preoperative levels significantly earlier, it was indicative of better functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…One clinical study demonstrated that a decrease of the postoperative platelet percentage to below 60% after hepatectomy was associated with delayed liver function recovery and postoperative morbidity (45). Although platelet counts reached a minimum on POD 3 for all patients (45), when platelet counts returned to preoperative levels significantly earlier, it was indicative of better functional recovery. In the current study, a significantly prolonged reduction in platelet count was observed for the PHx and bleeding group compared to PHx alone, which probably contributed to the observed delayed regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Lower platelet counts lead to poor graft regeneration but lower incidences of ischemia-reperfusion injury in partial grafts. Overall higher platelets counts are beneficial because their impact on liver regeneration outweighs the associated risk of ischemia-reperfusion injury, most notably during the early post-LDLT period[ 52 ]. Animal experiments to explain this phenomenon are still lacking, and basic studies and prospective clinical trials are warranted.…”
Section: Platelets and Ldltmentioning
confidence: 99%